RESTORATION OF A POST-SURGICAL DEFECT BY MAGNETIC MAXILLOFACIAL PROSTHESIS: A CASE REPORT - Muhammad Aamir Raﬁque; Khan, Safana; Hira Ahmed (Journal of University Medical & Dental College, 2020)
ABSTRACT: Edentulous patient with an intra-oral and extra-oral defect suﬀers from both functional loss and psychological distress. Magnets give a successful approach to rehabilitate the oral functions and improve the quality of life. This case report describes a simple method of fabricating a two part magnetic maxillofacial prosthesis.